Hubungan citra tubuh dengan gangguan makan pada remaja awal di Wilayah kerja Puskesmas Gamping 2 Sleman Yogyakarta - Fuadah, Luthfi; Hidayati, Rizqi Wahyu (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Increased awareness of body image images occurs in early adolescence. The majority of early adolescence are dissatisfied with their appearance. This is due to the changes that occur during puberty. Changes that occur are an increase in body fat, which can cause adolescents to control their body weight to get the ideal body shape. The aim of this study is to correlate between body image and eating disorders in early adolescents in the working area of ​​ Gamping 2 Public Health Center. This study used a cross-sectional approach. A total sample of 110 respondents was selected by convenience sampling technique. The inclusion criteria for this study were early adolescents aged 12-15 years with a Body Mass Index range of values ​​<17-25.0 or very thin to normal categories. While the exclusion criteria were adolescents who went on a diet because they suffered from illness, had digestive disorders with drastic weight loss for six months, and adolescents with a diagnosis of mental disorders. The research instrument was The Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBSRQ-AS) and the Eating Attitudes Test© (EAT-26) questionnaire. Data analysis used the Gamma correlation test. Based on the study, the result showed that there were any correlation between body image and eating disorders in early adolescents in the working area of ​​Gamping 2 Public Health Center, Sleman Yogyakarta, with a p-value of 0.00 (p>0.05) and a correlation value of 0.848. It means that they had strong correlation between body image and eating disorders in adolescents